2022
DOI: 10.1038/s41556-022-00878-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequential enhancer state remodelling defines human germline competence and specification

Abstract: Germline-soma segregation is a fundamental event during mammalian embryonic development. Here, we establish the epigenetic principles of human primordial germ cell (hPGC) development using in vivo hPGCs and stem cell models recapitulating gastrulation. We show that morphogen-induced remodelling of mesendoderm enhancers transiently confers the competence for hPGC fate, but further activation favours mesoderm and endoderm fates. Consistently, reducing the expression of the mesendodermal transcription factor (TF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 100 publications
3
61
0
Order By: Relevance
“…Furthermore, we observed upregulation of NANOG (p < 9.26e -48 /1.62e -6 ) and concomitant downregulation of OTX2 (p < 6.48e -10 /0.045) in subcluster 3 compared to non-competent clusters 1 and 22 respectively. Notably, OTX2 negatively regulates PGCLC competence in mice (Zhang et al, 2018) and we recently found that OTX2 has a similar function in the human germline (Tang et al, 2022)…”
Section: Detection Of Pgc Competent Populationmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we observed upregulation of NANOG (p < 9.26e -48 /1.62e -6 ) and concomitant downregulation of OTX2 (p < 6.48e -10 /0.045) in subcluster 3 compared to non-competent clusters 1 and 22 respectively. Notably, OTX2 negatively regulates PGCLC competence in mice (Zhang et al, 2018) and we recently found that OTX2 has a similar function in the human germline (Tang et al, 2022)…”
Section: Detection Of Pgc Competent Populationmentioning
confidence: 93%
“…We investigate how the precursor PreME cells gain competence for PGC-fate to address this. We also analysed the PGC-competent 4i cells against the non-competent populations (PSCs and ME) (Tang et al, 2022).…”
Section: Detection Of Pgc Competent Populationmentioning
confidence: 99%
“…As it was pointed above, the Sox17-Oct4 complex occupies compressed motifs, which are 1 bp shorter that the canonical Sox2-Oct4 motif [ 121 ]. Analyses of open chromatin during hPGC maturation have revealed the compressed Sox-Oct motif occurs across active DNA elements [ 146 , 147 ]. As Sox17 is associated with endoderm specification, the rationale for Oct4 partner switching from Sox2 to Sox17 in human PGC development remains unclear.…”
Section: Biological Functions Of the Pouv Proteins In Amniotesmentioning
confidence: 99%
“…We found that in addition to germ cell fate, the mesoderm and endoderm lineages were induced in the current differentiation system. A study in human PSCs revealed that predifferentiation through premesendoderm intermediate activates mesendoderm enhancers and endows human PSCs with competence for PGCLCs differentiation [ 41 ] and further activation induces mesoderm and endoderm lineage specification, whereas downregulation of mesendodermal marker gene OTX2 promotes the PGC’s fate. Moreover, the synergist interaction of SOX17 and TFAP2C guarantees the PGCLCs’ differentiation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in human PSCs revealed that predifferentiation through premesendoderm intermediate activates mesendoderm enhancers and endows human PSCs with competence for PGCLCs differentiation [ 41 ] and further activation induces mesoderm and endoderm lineage specification, whereas downregulation of mesendodermal marker gene OTX2 promotes the PGC’s fate. Moreover, the synergist interaction of SOX17 and TFAP2C guarantees the PGCLCs’ differentiation [ 41 ]. Taken together, it is worthy to test whether the same mechanism is used to induce mPGCLCs and the inhibition of the mesoderm and endoderm cell fates using small molecules could further improve the frequency of PGCLC differentiation from primate PSCs.…”
Section: Discussionmentioning
confidence: 99%